1974
DOI: 10.1017/s0022172400024086
|View full text |Cite
|
Sign up to set email alerts
|

The isolation of Escherichia coli from a poultry packing station and an abattoir

Abstract: SUMMARYThe distribution and serotype of strains of Escherichia coli from a poultry packing station and an abattoir are described. The results indicated that animal faecal strains contaminated the environment and the animal carcasses.Using 150 0 antisera, a high proportion of the E. coli strains were non-typable. This suggests that the serotype distribution of E. coli in animals is different from that in man.Strains with single antigenic differences were isolated, and the possibility of genetic transfer of thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
6
0

Year Published

1977
1977
2005
2005

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(7 citation statements)
references
References 3 publications
1
6
0
Order By: Relevance
“…This is consistent with contamination of animal carcasses with the host's fecal flora during slaughter and processing and with use of antimicrobial agents in food-animal production [13,14]. In contrast, produce and other miscellaneous food items (including cheeses, salami, delicatessen items, turkey franks, and pastry products) were comparatively devoid of E. coli.…”
Section: Discussionsupporting
confidence: 68%
“…This is consistent with contamination of animal carcasses with the host's fecal flora during slaughter and processing and with use of antimicrobial agents in food-animal production [13,14]. In contrast, produce and other miscellaneous food items (including cheeses, salami, delicatessen items, turkey franks, and pastry products) were comparatively devoid of E. coli.…”
Section: Discussionsupporting
confidence: 68%
“…Between 29 % and 63 % of the swabs examined yielded at least one non-typable isolate and in all three surveys there were a few swabs in which all isolates were non-typable. Shooter et al (1974) concluded that non-typables probably comprise O -serogroups as yet undefined, since 13 different H antigens were found among 509 isolates untypable by O-grouping sera. Non-typable and rough strains have been differentiated using phages (Budde, Nimmich & Naumann, 1978) while biotype and resistance pattern has been used to define non-typable E. coli (NTEC) strains .…”
Section: Serotypingmentioning
confidence: 99%
“…One of the problems associated with serotyping is that some isolates will be either non-typable or autoagglutinable (rough) and if the proportion happens to be large the value of the method is necessarily limited. Shooter et al (1974) serotyped 798 E. coli isolates from abattoirs with 150 0-antisera and found 509 (64 00) non-typable. This compared to only 2 (0-1 00) of 1580 human isolates.…”
Section: Serotypingmentioning
confidence: 99%
“…Retail poultry products are routinely heavily contaminated with avian fecal E. coli (40,43). Such E. coli, which can be antibiotic resistant (including to FQs) (14), widely contaminates kitchen surfaces during meal preparation, is not readily removed from these surfaces by standard cleaning procedures, and can subsequently be isolated from the feces of persons preparing the meals (10,30).…”
mentioning
confidence: 99%